Effect of maternal pre-pregnancy body mass index and gestational weight gain on birth weight and gestational age: An observational cross-sectional study - Mitra, Shaon; Arnab Mondal, (Asian Journal of Medical Sciences, 2024)
Background: Studies show that pre-pregnancy body mass index (ppBMI) and gestational weight gain (GWG) are associated with birth weight (BW), gestational age (GA), and neonatal morbidities. Higher BW leads to metabolic syndrome. Preterm and low BW (LBW) have short and long-term morbidities. Monitoring ppBMI and GWG is necessary as these are modifiable risk factors for obesity. In this study, we revisited these findings in an Indian scenario. Aims and Objectives: The primary objective is to study the association of BW and GA with ppBMI and GWG. The secondary objective is to study the association of ppBMI and GWG with cesarean section (CS), infant size, and early neonatal intensive care unit (NICU) requirement. Materials and Methods: This observational cross-sectional study was conducted over 1 year with 230 mothers, after Institutional Ethics Committee approval and informed consent. Data were collected using predesigned pro forma and analyzed by SPSS. Digital weighing scales, stadiometer, and fenton growth charts were used. Results: We found a positive linear correlation of ppBMI and GWG with BW. Obesity and excess GWG were associated with higher BW, large for GA, CS, and NICU stay. Overweight had more CS. Underweight and less GWG had a greater risk of LBW, preterm, and NICU stay. Less GWG had more small for GA. Conclusion: GWG and ppBMI are determinants of BW, GA, and neonatal morbidities. Further studies should focus on exercise and nutrition in pregnant and reproductive age women so that healthy babies with low-risk of obesity, metabolic syndrome, and neurodevelopmental disabilities are born.